2022
DOI: 10.1038/s41467-022-29192-w
|View full text |Cite
|
Sign up to set email alerts
|

Identifying regions for enhanced control of gambiense sleeping sickness in the Democratic Republic of Congo

Abstract: Gambiense human African trypanosomiasis (sleeping sickness, gHAT) is a disease targeted for elimination of transmission by 2030. While annual new cases are at a historical minimum, the likelihood of achieving the target is unknown. We utilised modelling to study the impacts of four strategies using currently available interventions, including active and passive screening and vector control, on disease burden and transmission across 168 endemic health zones in the Democratic Republic of the Congo. Median projec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The results of the model fitting for the models with and without animal transmission, in the form of 1 000 realisations from the joint posterior distribution of all fitted parameters, were used to make projections under two main strategies. These are a subset of those reported in the paper on projections for the model without animal transmission [ 30 ]. In both strategies, AS was continued beyond 2016 at the mean level observed in that health zone in the period 2012 to 2016, this was chosen as reflecting an achievable level of AS in that locale with recent, if not current, resource availability.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the model fitting for the models with and without animal transmission, in the form of 1 000 realisations from the joint posterior distribution of all fitted parameters, were used to make projections under two main strategies. These are a subset of those reported in the paper on projections for the model without animal transmission [ 30 ]. In both strategies, AS was continued beyond 2016 at the mean level observed in that health zone in the period 2012 to 2016, this was chosen as reflecting an achievable level of AS in that locale with recent, if not current, resource availability.…”
Section: Methodsmentioning
confidence: 99%
“…The year of elimination of transmission (EoT) is defined in our deterministic model as the first year in which less than one case is found, in line with the proxy threshold used to determine EoT in other gHAT modelling [35]. Whilst it is imperfect, this level of new infections has been found to be an adequate approximation of the threshold to simulate local extinction as characterized in comparisons with stochastic models [36].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the effectiveness of VC (measured by the annual reduction in tsetse population density) is between 80 and 99% [13, 2123]. Based on reported VC effectiveness, modelling exercises predict a rapid decline in underlying new infections when VC is used to supplement medical interventions and that EoT is expected to be achieved within four years of starting VC roll out [24].…”
Section: Methodsmentioning
confidence: 99%
“…Based on reported VC effectiveness, modelling exercises predict a rapid decline in underlying new infections when VC is used to supplement medical interventions and that EoT is expected to be achieved within four years of starting VC roll out [24].…”
Section: Current Interventionsmentioning
confidence: 99%
See 1 more Smart Citation